Assessing The Classroom Learning in Arabic Matriculation Program: Tutor and Student Perspective - Jundi, Muhammad; Ali, Mohommed (UIN ANTASARI, 2023)
The Arabic language matriculation program in the Arabic Education Department of IAIN Sultan Amai has been implemented for years, but its effectiveness and efficiency have not been scientifically evaluated yet. This study aims to evaluate the Arabic language matriculation program from the perspectives of tutors and students. The approach used is qualitative with a descriptive type of analysis, and the data sources are the tutors from each class and a number of students from different classes. Data collection methods used are interviews and observations. The results show that the strengths of the matriculation program are the dedication of tutors, varied teaching methods, customized handbooks, an Arabic language environment, and cooperative participants. However, the program also has weaknesses, such as unclear educational calendars, unstructured evaluations, and suboptimal attendance control. In conclusion, the roles of tutors and student management are vital in this program, and positive two-way feedback from participants and tutors can sustain the program despite shortcomings in management. It is suggested to conduct a study on the program's effectiveness and obtain empirical data in the form of quantitative measurement.